Tele-dentistry, its trends, scope, and future framework in oral medicine; a scoping review during January 1999 to December 2021 - Fatemeh Niknam; Roxana Sharifian; Azadeh Bashiri; Maryam Mardani; Reza Akbari; Haitham Tuffaha; Loc Do; Peivand Bastani (Archives of Public Health, 2023)
Abstract Background Tele-dentistry has been increasingly used for different purposes of visit, consultation, triage, screening, and training in oral medicine. This study aims to determine the main facilitators, barriers, and participants` viewpoints of applying tele-dentistry in oral medicine and develop a framework indicating the input, process, output, and feedback. Method This was a scoping review conducted in 2022 applying Arksey and O’Malley (2005) approach. Four databases including ISI web of science, PubMed, Scopus, and ProQuest were searched from January 1999 to December 2021. Inclusion criteria consisted of all original and non-original articles (reviews, editorials, letters, comments, and book chapters), and dissertations in English with a full text electronic file. Excel2016 was used for descriptive quantitative analysis and MAXQDA version 10 was applied for qualitative thematic analysis. A thematic framework was developed customizing the results of the review in a virtual mini expert panel. Results Descriptive results show that among 59 included articles, 27 (46%) have addressed the various applications of tele-dentistry during COVID-19 pandemic in the field of oral medicine. From geographical distribution perspective, most of the papers were published in Brazil (n = 13)/ 22.03%, India (n = 7)/11.86% and USA (n = 6)/10.17%. Thematic analysis shows that seven main themes of “information”, “skill”, “human resource”, ‘technical”, “administrative’, ‘financial’, and ‘training and education’ are explored as facilitators. ‘Individual’, ‘environmental’, ‘organizational’, ‘regulation’, ‘clinical’, and ‘technical barriers’ are also identified as main barriers of tele-dentistry in oral medicine. Conclusion According to the results for using tele-dentistry services in oral medicine, a diverse category of facilitators should be considered and at the same time, different barriers should be managed. Users` satisfaction and perceived usefulness of tele-dentistry as final outcomes can be increased considering the system`s feedback and applying facilitator incentives as well as decreasing the barriers.